Focus group discussion: a tool for health and medical research - Wong, L.P. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2008)
Focus group discussion is a research methodology in which a small group of participants gather to discuss a specified topic or an issue to generate data. The main characteristic of a focus group is the interaction between the moderator and the group, as well as the interaction between group members. The objective is to give the researcher an understanding of the participants' perspective on the topic in discussion. Focus groups are rapidly gaining popularity in health and medical research. This paper presents a general introduction of the use of focus groups as a research tool within the context of health research, with the intention of promoting its use among researchers in healthcare. A detailed methodology for the conduct of focus groups and analysis of focus group data are discussed. The potentials and limitations of this qualitative research technique are also highlighted.